2018
DOI: 10.3892/or.2018.6694
|View full text |Cite
|
Sign up to set email alerts
|

Biological functions and clinical significance of the newly identified long non‑coding RNA RP1‑85F18.6 in colorectal cancer

Abstract: The biological functions of long non-coding RNAs (lncRNAs) in cancer have not been fully elucidated. The present study demonstrated that the expression of a newly identified lncRNA, RP1-85F18.6, was upregulated in colorectal cancer (CRC) tissues and cell lines. Knockdown of lncRNA RP1-85F18.6 served a key role in tumor inhibition, reduced cell proliferation and invasion, disrupted the cell cycle, and increased apoptosis and pyroptosis of CRC cells. Conversely, overexpression of lncRNA RP1-85F18.6 exerted the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 38 publications
(44 reference statements)
0
58
0
Order By: Relevance
“…In addition, compared to wild-type (WT) littermates, Casp11 −/− mice are highly vulnerable to the AOM/DSS model of CAC 70 . GSDMA was not expressed in normal colorectal epithelial cells but was gradually overexpressed in carcinoma cells, while GSDMD exhibited the opposite trend 71,72 . Gsdmc is not detected in normal colorectal tissues but is present in CRC tissues.…”
Section: Role Of Pyroptosis In Tumorigenesis and Metastasismentioning
confidence: 90%
“…In addition, compared to wild-type (WT) littermates, Casp11 −/− mice are highly vulnerable to the AOM/DSS model of CAC 70 . GSDMA was not expressed in normal colorectal epithelial cells but was gradually overexpressed in carcinoma cells, while GSDMD exhibited the opposite trend 71,72 . Gsdmc is not detected in normal colorectal tissues but is present in CRC tissues.…”
Section: Role Of Pyroptosis In Tumorigenesis and Metastasismentioning
confidence: 90%
“…The subsequent study showed that the effect of the pathway on the cell cycle was mediated by cyclin proteins. As cyclin A regulates the S phase [ 41 ] and cyclin B regulates the G2 phase[ 42 ], emodin decreased cyclin A and B which results in the decrease in cells at the S/G2 phase. Cyclin C was proved to suppressed cancer [ 43 ], it is also a downstream target of emodin found by this study.…”
Section: Discussionmentioning
confidence: 99%
“…Long non-coding ribonucleic acid (LncRNAs) is also involved in the regulation of pyroptosis. Ma et al (81) showed that inhibition of IncRNARP1-85F18.6 could promote the pyroptosis of colorectal cancer cells by modulating the expression level of ΔNp63. In addition, IncRNARP1-85F18.6, ΔNp63, and GSDMD also have certain value in the prognosis and diagnosis of colorectal cancer.…”
Section: Pyroptosis In Cancermentioning
confidence: 99%